Perancangan Iklan Komersil CV. Matiinu Berdikari Berbasis Animasi 2D - Muhammad Iqbal Erfand; Syafei Syafei (Imajinasi : Jurnal Ilmu Pengetahuan, Seni, dan Teknologi, 2024)
CV. Matiinu Offset is a printing company located in the city of Pekanbaru, on Jalan Nenas which has a lot of competition. When the Covid-19 pandemic occurred, many companies, business people, take-out shops, entrepreneurs and others experienced a decline in turnover, including printing companies. Therefore, the author wants to help CV printing companies a little. Matiinu Offset to start rising again, one of which is by making 2D animation as a commercial advertisement to help the development of CV. Offset Matiinu. The manufacturing method is frame by frame, which is a method for creating the illusion of movement using an arrangement of several different images in each frame. Frame animation is a very simple form of animation that displays a sequence of images that alternate quickly.